Searching for the effects of momentum in beach volleyball: An empirical comparison of different models - Lillich, L.; Schweizer, G.; Nießner, M. (Zeitschrift für Sportpsychologie, 2023)
Abstract: The goal of the present study was to investigate whether in a beach volleyball game between teams of equally skilled players, a team is more likely to win a three-set match if it has won the second set than if it has won the first one. Furthermore, we analyzed how many games end after two or after three sets. We compared three models making different predictions: the psychological momentum model (PMM), the strategic effects model (SEM), and the independent probability model (IPM). In line with the PMM and the SEM, the results showed that regardless of how strictly we controlled for ability, there were always significantly more two-set than three-set matches (33 - 44 % three-set matches). In line with the SEM, but not the PMM, the analysis of almost 1,000 three-set matches between equally skilled players suggested that in a third set neither the winner of the first nor the winner of the second set has an advantage in the third set.